Politik Islam di Indonesia: Ideologi, Transformasi dan Prospek dalam Proses Politik Terkini - Zulifan, Muhammad (Political Science Program, Universitas Negeri Semarang, 2016)
This study examines the correlation between Islamic doctrine of the concept of state and government system with the ambition of some Muslims to revive sharia values in a country. Literature research methodology is employed to explore ideas of Islamic political thinkers, ranging from classical and medieval, era such as al-Farabi, al-Mawardi, Ibn Taymiyyah, to the modern era and contemporary scholars, such as al-Attas, Fazlur Rahman, and Arkoun. The validity of the democratic system and the form of an ideal state for Muslims are debatable among Muslim scholars. The concept of civil society that becomes a manifestation of civil society is believed to have been practiced in the historical period of Islamic government.